Practical Implementation of the Competence-based Approach on Innovation - type Lectures - Solovjova, Tatjana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The paper presents the methodology of lectures of an innovative type. It is aimed at developing students' instrumental competences (ability to process information: create an associative array, paraphrase, interpret, assign to a concept; ability to organize information: to identify, differentiate, classify, establish a consequence, forecast; ability to analyze verbal and visual information; ability to find inconsistencies in reasoning, etc.). Understanding of educational information by students is rooted in self-study of the trainees, which creates conditions for development of their instrumental competences during the lectures. Learning outcomes in the intellectual and developmental education space is evaluated not according to the amount of information, given at the lecture, but to the depth of students’ understanding of this information and development of their instrumental competences, determining their ability to further self-education.